Polyfluorinated carba-closo-dodecaboranes with amino and ammonio substituents bonded to boron. Issue 45 (14th July 2015) - Konieczka, Szymon Z.; Drisch, Michael; Edkins, Katharina; Hailmann, Michael; Finze, Maik
Abstract : The three isoelectronic inner salts 1-H- x -H3 N- closo -1-CB11 F10 ( x = 12, 7, 2) are accessible by fluorination of x -H3 N- closo -1-CB11 H11 ( x = 12, 2) and 7-H3 N-12-F- closo -1-CB11 H10, respectively. Deprotonation of the decafluorinated ammoniocarba- closo -dodecaboranes yields the corresponding aminocarba- closo -dodecaborate anions [1-H- x -H2 N- closo -1-CB11 F10 ] − ( x = 12, 7, 2). Abstract : The inner salts x -H3 N- closo -1-CB11 H11 ( x = 12, 2) and 7-H3 N-12-F- closo -1-CB11 H11 were fluorinated with elemental fluorine in anhydrous hydrogen fluoride to give the B-perfluorinated ammonio derivatives 1-H- x -H3 N- closo -1-CB11 F10 ( x = 12, 7, 2). Deprotonation of the ammonio group yielded the corresponding amino-functionalized anions [1-H- x -H2 N- closo -1-CB11 F10 ] − ( x = 12, 7, 2) that were isolated as [Et4 N] + salts. Hydrolysis of the highly fluorinated inner salts 1-H- x -H3 N- closo -1-CB11 F10 ( x = 12, 7, 2) is very slow in acidic aqueous solutions. This stability of the ammonio derivatives is unprecedented because the related fluorinated anion [1-H2 N- closo -1-CB11 F11 ] − is immediately hydrolyzed to simple boron species in the presence of aqueous acids. The ammonio derivatives 1-H- x -H3 N- closo -1-CB11 F10 ( x = 12, 7, 2) are much more acidic compared to their non-fluorinated counterparts as assessed from potentiometric titrations and DFT calculations. The inner salts and the anions were characterized by NMR and vibrational sepectroscopy. Solid-sate structures of 1-H-12-H3 N- closo -1-CB11 F10 ·H2 O, 1-H-7-H3 N- closo -1-CB11 F10 ·diglyme, 1-H-2-H3 N- closo -1-CB11 F10 ·0.5H2 O, 7-H3 N-12-F- closo -1-CB11 H10 ·(CH3 )2 CO and [Et4 N][1-H-12-H2 N- closo -1-CB11 F10 ] were determined by single-crystal X-ray diffraction.